Simultaneous imaging of ultrasonic relative backscatter and attenuation coefficients for quantitative liver steatosis assessment - Timana, J.; Chahuara, H.; Basavarajappa, L.; Basarab, A.; Hoyt, K.; Lavarello Montero, R. (Nature Research, 2023)
Prevalence of liver disease is continuously increasing and nonalcoholic fatty liver disease (NAFLD) is the most common etiology. We present an approach to detect the progression of liver steatosis based on quantitative ultrasound (QUS) imaging. This study was performed on a group of 55 rats that were subjected to a control or methionine and choline deficient (MCD) diet known to induce NAFLD. Ultrasound (US) measurements were performed at 2 and 6 weeks. Thereafter, animals were humanely euthanized and livers excised for histological analysis. Relative backscatter and attenuation coefficients were simultaneously estimated from the US data and envelope signal-to-noise ratio was calculated to train a regression model for: (1) fat fraction percentage estimation and (2) performing classification according to Brunt’s criteria in grades (0 <5%; 1, 5–33%; 2, >33–66%; 3, >66%) of liver steatosis. The trained regression model achieved an R² of 0.97 (p-value < 0.01) and a RMSE of 3.64. Moreover, the classification task reached an accuracy of 94.55%. Our results suggest that in vivo QUS is a promising noninvasive imaging modality for the early assessment of NAFLD.
Keywords: Steatosis; Nonalcoholic fatty liver disease; Fatty liver; Ultrasound; Medicine; Choline; Ultrasound imaging; Liver disease; Internal medicine; Nuclear medicine; Artificial intelligence; Radiology; Computer science; Disease; https://purl.org/pe-repo/ocde/ford#3.02.00